Lebanon : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Lebanon. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Lebanon is facing a difficult global, regional, and domestic environment simultaneously for the first time in more than a decade. Domestic policies should aim at instilling confidence and tackling key policy challenges, such as preserving macroeconomic stability and paving the way for a more resilient, dynamic, and inclusive economy. The Banque du Liban (BdL) relied on its large foreign reserves build-up during the upswing to intervene forcefully when the Lebanese pound came under pressure from deposit outflows and currency conversions in the wake of the government crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet